IMPLEMENTASI PENDEKATAN TEKNOLOGI DALAM PENGEMBANGAN KURIKULUM MERDEKA DI SEKOLAH DASAR - Prasetyo, Arif (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
Curriculum development with a technology approach is one of several approach models in curriculum development. The technological approach is considered very relevant to be applied in MI/SD schools because we have now entered the era of the industrial revolution. Therefore, in curriculum development in MI/SD elementary schools, it is necessary to implement a technological approach in curriculum development. In fact, currently an independent curriculum is being implemented which aims to give students greater freedom in determining the course of their learning. This research aims to explore and analyze the use of technological approaches in developing an independent curriculum in elementary schools. The research was carried out using literature and qualitative review methods, namely looking for data from relevant previous research sources, then in-depth interviews with elementary/MI teachers who have implemented a technological approach to the independent curriculum. The research results show that the implementation of a technological approach can increase the effectiveness and efficiency of learning, and can facilitate students in achieving the learning goals that have been set. However, several obstacles were also found, such as minimal access to technology in the surrounding environment or difficulties in integrating technology into the curriculum as a whole. Therefore, the author recommends the need for support from various parties to make the implementation of a technological approach an important part of developing an independent curriculum in elementary schools